Gene Environment Interactions in the Etiology of Neural Tube Defects - Finnell, Richard H.; Caiaffa, Carlo Donato; Kim, Sung-Eun; Lei, Yunping; Steele, John; Cao, Xuanye; Tukeman, Gabriel; Lin, Ying Linda; Cabrera, Robert M.; Wlodarczyk, Bogdan J. (Frontiers in Genetics, 2021)
Human structural birth defects are the leading cause of infant mortality in the USA. The Center for Disease Control (CDC) estimates that 1 of every 33 US newborns present with a birth defect in the US; the worldwide the estimate approaches 6% of infants presenting with congenital anomalies. The scientific community has recognized for decades that the vast majority of birth defects have undetermined etiologies, although we propose that environmental agents interacting with inherited susceptibility genes are the major contributing factors. Among the most common and debilitating of human birth defects are those affecting the closure of the neural tube closure, the precursor to the central nervous system. These malformations will be the focus of this review. Neural tube defects (NTDs) result from failures in embryonic central nervous system development and include posterior defects (spina bifida), anterior defects (anencephaly, encephalocele, iniencephaly), or disruption along the entire neural tube (craniorachischisis). Globally, these defects are estimated to affect approximately 18.6 per 10,000 live births. Up to 70% of NTDs are attributed to genetic factors, while the intrauterine environment tips the balance towards neurulation failure in at risk individuals. Despite aggressive campaigns for folic acid supplementation and fortification of the US food supply, NTDs still affect up to 2,300 US births annually and some 166,000 spina bifida patients currently live in the US, more than half of whom are now adults. Within the context of this review, we will consider the role of maternal nutritional status (deficiency states involving B vitamins and one carbon analytes) and potential modifiers of NTD risk beyond folic acid. There are several well-established human teratogens that contribute to the population burden of NTDs, including: industrial waste and pollutants (e.g. arsenic, pesticides, polycyclic aromatic hydrocarbons (PAHs)), pharmaceuticals (e.g. anti-epileptic medications), and maternal hyperthermia during the first trimester. Animal models for these teratogens are described with attention focused on valproic acid (VPA; Depakote). Genetic interrogation of model systems involving VPA will be used as a model approach to discerning susceptibility factors that define the gene-environment interactions contributing to the etiology of NTDs.